Principal's Behavior in Strengthening Teacher Innovation and Creativity During The Covid-19 Pandemic - Tatang Ibrahim; Siti Insani Akbari; Siti Suaidah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The purpose of this article, among others, was to analyze the role of the principal in increasing teacher innovation and creativity at SMPIT Hidayatul Ghazzali Purwakarta during a pandemic. This research was conducted with a qualitative approach and data collection through observation and interviews with the aim of describing the role of the principal at SMPIT Hidayatul Ghazzali. The objects of research include the principal, three teachers, the school committee, and two guardians and students. The role of the principal as a leader or leader, it can be seen that some of the efforts he has made in increasing teacher innovation and creativity in learning include: a) the principal as an example; b) providing guidance or supervision; c) award and punishment; d) involving teachers in training; e) create a pleasant working atmosphere, and f) provide freedom to innovate and be creative.